Applying the Moodle system in teaching contemporary art : Primjena sustava Moodle u poučavanju suvremene umjetnosti - Tomaš, Suzana (Array, 2021)
The development of modern technologies, applying pedagogical principles, has enabled a new educational paradigm of e-learning, which rep-resents quality support to teachers in the transfer of knowledge. This paper presents the possibilities of applying an e-learning system in teaching visual arts, precisely in teaching contemporary art. Well-designed and applied teaching content in an e-learning system enables various scenarios of learning, teaching, and testing the knowledge of contemporary art. Contemporary art thus becomes a communication within which the observer becomes an interpreter of the different levels of meaning of an artwork. This re-search, designed as an educational experiment, involved 57 students from two primary schools in Split-Dalmatia County. We found differences in the knowledge and preferences of fourth graders regarding contemporary art with respect to teaching methods. The results show increasing student preferences for contemporary art in a group using the Moodle system and in a group of students creating inspired by contemporary art-works. Students expressed satisfaction with learning about contemporary art using Moodle. The difference between the results of the initial and final testing of knowledge showed statistical significance in the groups that had art lessons. Moodle provides opportunities to learn a variety of content, including contemporary art in primary school.